2006
DOI: 10.1007/s10608-006-9023-z
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Performance as a Mediator in the Relationship Between Social Anxiety and Negative Post-Event Rumination

Abstract: This study tested D. M. Clark and A. Wells' (1995) proposition that negative postevent rumination is produced by negative self perceptions formed by socially phobic individuals during anxiety-provoking events. A socially phobic group and a nonanxious control group performed an impromptu speech, and appraised their performance immediately afterwards. One week later, participants were assessed as to how frequently they had had negative thoughts about the speech, how much they engaged with these thoughts, how dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
68
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 45 publications
9
68
1
Order By: Relevance
“…Poorer self-appraisal of performance uniquely predicted greater levels of post-event rumination 1 week after the speech. Perini et al (2006) replicated these results and further found that self-appraisal of performance fully mediated the relationship between social anxiety and post-event rumination, such that, when performance appraisal was statistically controlled, the relationship between social anxiety and post-event rumination was no longer significant. This finding indicates that one's perception of their performance may be a key factor in understanding the rumination process.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Poorer self-appraisal of performance uniquely predicted greater levels of post-event rumination 1 week after the speech. Perini et al (2006) replicated these results and further found that self-appraisal of performance fully mediated the relationship between social anxiety and post-event rumination, such that, when performance appraisal was statistically controlled, the relationship between social anxiety and post-event rumination was no longer significant. This finding indicates that one's perception of their performance may be a key factor in understanding the rumination process.…”
Section: Introductionmentioning
confidence: 57%
“…Recent research indicates that self-appraisals of performance are the most likely unique predictor of post-event rumination within clinical samples of SAD participants (Abbott and Rapee 2004;Chen et al 2013;Perini et al 2006;Zou and Abbott 2012). Abbott and Rapee (2004) asked participants to complete a 3-min speech and a measure of performance self-appraisal (Performance Questionnaire; Rapee and Lim 1992) 1 week prior to assessing negative rumination (Thoughts Questionnaire; Abbott and Rapee 2004;Edwards et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…According to Clark and Wells (1995), socially anxious individuals will engage in PEP if they experience such negative cognitions during the situation. In support of this hypothesis, Perini et al (2006) found that socially anxious individuals engaged in PEP only if they appraised their performance negatively. Thus the present study investigated whether negative social cognitions during a social situation predict whether individuals engage in negative PEP.…”
Section: The Type Of Social Situationmentioning
confidence: 81%
“…Studies have shown that socially anxious subjects tend to utilise state anxiety sensations to make negative inferences of their appearance and performance, and the level of danger in a social situation (Arntz et al 1995;Mansell and Clark 1999). Given that negative performance appraisals are an important predictor of PEP (Perini et al 2006), state anxiety may be associated with greater PEP, particularly among high socially anxious individuals. However the study by McEvoy and Kingsep (2006) had several limitations: state anxiety was assessed with a single-item questionnaire, anxiety was assessed retrospectively thereby introducing memory biases, and their sample only contained social phobia patients.…”
Section: The Type Of Social Situationmentioning
confidence: 99%
“…To illustrate, Rachman et al (2000) found that compared to low socially anxious individuals, high socially anxious individuals engaged in significantly more post-event rumination about unsatisfactory social events. Abbott and Rapee (2004), and Perini et al (2006) reported that higher levels of social anxiety were associated with more post-event rumination. Furthermore, Vassilopoulos (2004) reported a positive association between social anxiety and anticipatory processing, even when controlling for depression and trait anxiety.…”
Section: Introductionmentioning
confidence: 97%